Assessment of natural coagulants to remediate Tunisian textile wastewater by combining physicochemical, analytical, and toxicological data - Methneni, Nosra; Anthonissen, Roel; Van de Maele, Jolien; Trifa, Fatma; Verschaeve, Luc; Mansour, Hedi Ben; Mertens, Birgit (Environmental science and pollution research international, 2020)
Due to the complexity and variability of textile wastewater composition, a constant search for new treatment strategies that are efficient, eco-friendly, and cost-effective is mandatory. In the present study, the efficiency of coagulation-flocculation using biocoagulants derived from cactus Opuntia ficus indica and eggplant Solanum melongena to remove toxic compounds from Tunisian textile wastewater samples was evaluated by combining assays to investigate physicochemical properties and in vitro (geno)toxicity with analytical chemistry. Both natural coagulants could significantly improve the physicochemical properties of the textile wastewater samples compared to the traditionally used chemical coagulant. The highest rate of decolorization was achieved after treatment with the cactus-derived coagulant. The analytical study revealed the presence of only crystal violet dye (CV) in only one sample. Both natural coagulants were able to remove CV, which may (partially) explain the decolorization of the treated samples. Only one untreated textile effluent induced a genotoxic response in the VITOTOX ® assay. The genotoxic effect was not linked to the presence of CV and was no longer observed after treatment with each of the natural coagulants, suggesting the effectiveness of the remediation treatments to remove potentially genotoxic compound(s). However, in the other genotoxicity tests, no biologically relevant effects were observed for any of the tested samples. In conclusion, although the physicochemical data indicate that the use of natural coagulants (cactus and eggplant) could be an interesting alternative treatment process to the chemical coagulant for detoxifying textile effluents, these results were only partially supported by the toxicological and analytical data.